Impact of Surgeon Experience During Carotid Endarterectomy Operation and Effects on Perioperative Outcomes - Volkan Yüksel; Ahmet Coskun Ozdemir; Serhat Huseyin; Orkut Guclu; Fatma Nesrin Turan; Suat Canbaz (Brazilian Journal of Cardiovascular Surgery)
Abstract Objective: We evaluated the effect of surgeon experience on complication and mortality rates of carotid endarterectomy operation. Methods: Fifty-nine consecutive patients who underwent carotid endarterectomy between January 2013 and February 2016 were divided into two groups. Patients who had been operated by surgeons performing carotid endarterectomy for more than 10 years were allocated to group 1 (experienced surgeons; n=34). Group 2 (younger surgeons; n=25) consisted of patients operated by surgeons independently performing carotid endarterectomy for less than 2 years. Both groups were compared in respect of operative results and postoperative complications. Results: No intergroup difference was found for laterality of the lesion or concomitant coronary artery disease. In group 1, signs of local nerve damage (n=2; 5.9%) were detected, whereas in group 2 no evidence of local nerve damage was observed. Surgeons in group 1 used local and general anesthesia in 3 (8.8%) and 31 (91.2%) patients, respectively, while surgeons in group 2 preferred to use local and general anesthesia in 1 (4%) and 24 (96%) patients, respectively. Postoperative stroke was observed in group 1 (n=2; 5.9%) and group 2 (n=2; 5.8%). Conclusion: Younger surgeons perform carotid endarterectomy with similar techniques and have similar results compared to experienced surgeons. Younger surgeons rarely prefer using shunt during carotid endarterectomy. The experience and the skills gained by these surgeons during their training, under the supervision of experienced surgeons, will enable them to perform successful carotid endarterectomy operations independently after completion of their training period.